Konsep Pendidikan Akhlak Menurut Ibnu Miskawaih - Miswar, Miswar (STAI Serdang Lubuk Pakam, 2020)
This study aims to analyze Ibn Miskawaih's thoughts on moral education. This research uses qualitative methods with a literature-based approach. Data collection was carried out by exploring Ibn Miskawaih's thoughts as contained in his works, the main data sources came from his work of tahzibul Akhlak, and the supporting data sources came from other works, and books and journals related to his thoughts. The results showed that according to Ibn Miskawaih, morals are mental states that invite someone to do actions without thinking and being taken into account. So that it can be used as human nature and the results of the actions that have been done, become self-righteousness that can give birth to good khuluq. Miskawaih was not only a philosopher but he was a moralist, writer, chemist, historian. So that the work that he produces is not only about one scientific aspect. According to Ibn Miskawayh, the goal of moral education is the realization of an inner attitude that is able to spontaneously encourage the birth of all righteous deeds to achieve perfection and obtain true and perfect happiness. The goal of moral education formulated by Ibn Miskawaih is the realization of an inner attitude that is able to spontaneously induce all actions of good value. So as to achieve perfection and obtain true happiness that is perfect and complete.